IMPLEMENTING PEACE PEDAGOGY IN THE ASWAJA CURRICULUM: DEVELOPING STUDENTS' TOLERANT CHARACTER - Ulfi Fadli, Muhammad; Raharjo, Raharjo; Kurniyah, Kurniyah (Sekolah Tinggi Agama Islam Al Hidayah, 2025)
Background: This study is motivated by the ongoing challenges of intolerance among students and the need for Nahdlatul Ulama-based educational institutions to strengthen religious moderation through the Aswaja curriculum. Purpose: The study aims to describe the implementation of peace pedagogy in the Aswaja curriculum and analyze its contribution to the development of tolerant character among students at Madrasah Aliyah D-Baito Temanggung. Method: The research used a qualitative field study method with participants including the headmaster, Aswaja teachers, and students; data were collected through observation, semi-structured interviews, and document studies, then analyzed thematically using the Miles & Huberman interactive model with source and method triangulation. Hasil: The findings show that peace pedagogy is integrated into school policies, teaching practices, and school culture; the values of tawasuth, tasamuh, tawazun, and i‘tidal are internalized through reflective, dialogical, and collaborative learning, with teachers acting as facilitators of peace awareness, resulting in an increase in religious moderation understanding, social empathy, and tolerant attitudes in daily interactions. Conclusion: In conclusion, peace pedagogy is a strategic approach to developing a humanistic and moderate Aswaja curriculum while fostering a peaceful culture in madrasahs. Implication: Its implications suggest that schools/policy makers need to include peace-tolerance indicators in lesson planning, strengthen teacher training, and develop school culture to ensure sustainable implementation and replicability in other similar Islamic educational institutions.